Demystifying the persistent pneumothorax: role of imaging - Chaturvedi, Apeksha (Insights Imaging, 2016)
Evaluation for pneumothorax is an important indication for obtaining chest radiographs in patients who have had trauma, recent cardiothoracic surgery or are on ventilator support. By definition, a persistent pneumothorax constitutes ongoing bubbling of air from an in situ chest drain, 48 h after its insertion. Persistent pneumothorax remains a diagnostic dilemma and identification of potentially treatable aetiologies is important. These may be chest tube related (kinks or malposition), lung parenchymal disease, bronchopleural fistula, or rarely, oesophageal-pleural fistula. Although radiographs remain the mainstay for diagnosis and follow up of pneumothorax, computed tomography (CT) is increasingly being used for problem solving. Aetiology of persistent air leak determines the optimal treatment. For some, a simple repositioning of the chest tube/drain may suffice; others may require surgery. In this pictorial review, we will briefly describe the physiology of pneumothorax, discuss imaging features of identifiable causes for persistent pneumothorax and provide a brief overview of treatment options. Specific aetiology of a persistent air leak may often not be immediately discernible, and will need to be carefully sought. Accurate interpretation of imaging studies can expedite diagnosis and facilitate prompt treatment. Key points • Persistent pneumothorax is defined as a leak persisting for more than 2 days. • Radiographs can identify chest-tube-related causes of pneumothorax. • CT is the most useful test to identify other causes. • Penetrating thoracic injury can cause fistulous communication resulting in a persistent pneumothorax. • Discontinuity of visceral pleura identified by CT may indicate a bronchopleural fistula.